2021
DOI: 10.3389/fimmu.2021.740571
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Methylomic Landscape of Lung Tissues in Murine Acute Allergic Asthma

Abstract: Allergic asthma is well known as a common respiratory disorder comprising an allergic inflammatory nature and excessive immune characteristic. N6-methyladenosine (m6A) methylation is an RNA epigenetic modification that post-transcriptionally regulates gene expression and function by affecting the RNA fate. Currently, m6A methylation is gaining attention as a mechanism of immunoregulation. However, whether m6A methylation engages the pathological process of asthma remains uncertain. Here, we present the m6A met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 102 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…Accordingly, YT521-B homology (YTH) domain family is the main “readers” ( Jones et al, 2022 ) and “erasers” consisting of FTO and ALKBH5 ( Kaur et al, 2022 ). Recent studies have focused on the importance of m6A modification in tumors ( Jiang et al, 2022 ; Ma et al, 2022 ; Xiong et al, 2022 ; Yadav et al, 2022 ) and non-neoplastic diseases like asthma and pulmonary hypertension ( Teng et al, 2021 ; Zeng et al, 2021 ; Zhou et al, 2021 ). Nevertheless, the expression pattern of m6A regulators in CHP and IPF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, YT521-B homology (YTH) domain family is the main “readers” ( Jones et al, 2022 ) and “erasers” consisting of FTO and ALKBH5 ( Kaur et al, 2022 ). Recent studies have focused on the importance of m6A modification in tumors ( Jiang et al, 2022 ; Ma et al, 2022 ; Xiong et al, 2022 ; Yadav et al, 2022 ) and non-neoplastic diseases like asthma and pulmonary hypertension ( Teng et al, 2021 ; Zeng et al, 2021 ; Zhou et al, 2021 ). Nevertheless, the expression pattern of m6A regulators in CHP and IPF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes are proficient catalysts that continuously and efficiently catalyze the production of substrates 26,27 . There is growing evidence that RNA modification plays important roles in asthma progression 28 . Teng et al .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 There is growing evidence that RNA modification plays important roles in asthma progression. 28 Teng et al found that OVA-induced asthmatic mice had a specific pattern of m 6 A methylation modification compared to healthy mice. 28 Further investigation found that these differentially methylated mRNAs were closely related to immune function, such as inflammatory response, innate immune response, positive regulation of T cell activation, and hematopoietic cell lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout life, m 6 A-modified mRNAs play a role in variety of physiological activities, developmental processes and disease pathologies ( 7 , 8 ). Multiple diseases, such as heart failure ( 9 ), type 2 diabetes ( 10 ), kidney injury ( 11 ) and asthma ( 12 ) and various malignancies are associated with changes in m 6 A methylation.…”
Section: Introductionmentioning
confidence: 99%